2022
DOI: 10.1037/adb0000810
|View full text |Cite
|
Sign up to set email alerts
|

Daily variation in the patterns and characteristics of adolescent ENDS use.

Abstract: Objective: Adolescents are more likely than young adults to use electronic nicotine delivery systems (ENDS), yet most of what is known is concluded from young adult ENDS use as young adults are easier to survey. Additionally, while evidence about the prevalence and trends of adolescent ENDS use comes from crosssectional studies, ecological momentary assessment (EMA) studies provide greater detail about the ways in which adolescents vape and the environments that are favorable to adolescent vaping, providing im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…All models statistically controlled for age, biological sex, white race, spending money per week, and day type (weekday vs. weekend). Preliminary analyses suggested that the weekday (i.e., Sunday 4 p.m. through Friday 4 p.m.) vs. weekend (Friday 4 p.m. to Sunday 4 p.m.) contrast explained much of the variability in the day of the week [21]. The effect size r (or r = [(t 2 )/(t 2 + df )] 5 for Gaussian models and r = z/N 5 for dichotomous models) [30] with 95% confidence intervals was calculated to examine the magnitude of the effects.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…All models statistically controlled for age, biological sex, white race, spending money per week, and day type (weekday vs. weekend). Preliminary analyses suggested that the weekday (i.e., Sunday 4 p.m. through Friday 4 p.m.) vs. weekend (Friday 4 p.m. to Sunday 4 p.m.) contrast explained much of the variability in the day of the week [21]. The effect size r (or r = [(t 2 )/(t 2 + df )] 5 for Gaussian models and r = z/N 5 for dichotomous models) [30] with 95% confidence intervals was calculated to examine the magnitude of the effects.…”
Section: Discussionmentioning
confidence: 99%
“…Eligibility criteria for the first study included youth between 13 and 17 years of age who lived within 100 miles of Louisville, KY and reported vaping nicotine in the past two weeks on a screener. Additional details on the sample and methods are published elsewhere [20,21]. Of these 50 youth, 35 participated in the follow-up study.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations